Manifestasi Pelestarian Seni Budaya Sunda Ditengah Pandemi Covid-19 - Ai Novitasari; Mohamad Subur Drajat (Bandung Conference Series: Public Relations, 2022)
Abstract. Preservation of Sundanese culture and arts is the main focus of LSBS Unisba in carrying out an activity because it is one of the objectives of the Sundanese Cultural Arts Environment, the preservation of Sundanese culture and arts also needs to be done so that new generations are not blind to culture, especially Sundanese. With the existence of culture, norms and customs in society, it is much more attached or it can be said that society can be more prosperous with a good culture, while in art everyone can use it as a means of self-expression. That's what made the writer interested in taking the title "Manifestation of Preserving Sundanese Cultural Arts in the midst of the Covid-19 Pandemic" with the subtitle Case study regarding communication activities in the Sundanese Cultural Arts Environment, Bandung Islamic University in the manifestation program for the preservation of Sundanese culture in the midst of the covid-19 pandemic in the Kelurahan. Kopo, District Bojongloa Kaler, Bandung City. The purpose of this paper is to find out how the communication activities of LSBS Unisba with the community in the Kopo Village, Bojongloa Kaler District, Bandung City, how the intercultural communication of the LSBS of the Islamic University of Bandung with the community in the Kopo Village and also to find out why the LSBS of the Islamic University of Bandung organizes the preservation of Sundanese culture and arts. By using the theory of social interaction, and also the method of writing qualitative case studies. Data was collected through observation and in-depth interviews. An interactive model consisting of data reduction, data presentation and conclusion drawing is used to process data from observations and in-depth interviews. From this the authors found that there is verbal and nonverbal communication, there is a communication strategy in three areas of training, cooperation, assimilation and accommodation as a way of solving obstacles besides that there are also differences in background that foster LSBS Unisba's concern for Sundanese Arts and Culture, where Sundanese culture able to encourage positive activities while art is used as a means of self-expression. Abstrak. Pelestarian kebudayaan dan kesenian Sunda merupakan fokus utama LSBS Unisba dalam melakukan suatu kegiatan karena itu merupakan salah satu tujuan adanya Lingkung Seni Budaya Sunda, pelestarian kebudayaan dan kesenian Sunda juga perlu dilakukan agar generasi-generasi baru tidak buta akan budaya khususnya kesundaan. Dengan adanya budaya, norma dan adat dimasyarakat jauh lebih melekat atau dapat dikatakan masyarakat bisa lebih sejahtera dengan adanya budaya yang baik sedangkan dalam seni setiap orang dapat menggunakannya sebagai sarana ekspresi diri. Hal itulah yang membuat peneliti tertarik untuk mengambil judul “Manifestasi Pelestarian Seni Budaya Sunda ditengah Pandemi Covid-19” dengan sub judul Studi kasus mengenai aktivitas komunikasi Lingkung Seni Budaya Sunda Universitas Islam Bandung dalam program manifestasi pelestarian seni budaya Sunda ditengah pandemi covid-19 di Kelurahan Kopo Kecamatan Bojongloa Kaler Kota Bandung. Tujuan penelitian ini adalah untuk mengetahui bagaimana kegiatan komunikasi LSBS Unisba dengan masyarakat di Kelurahan Kopo Kecamatan Bojongloa Kaler Kota Bandung, bagaimana komunikasi antar budaya LSBS Universitas Islam Bandung dengan masyarakat di Kelurahan Kopo dan juga mengetahui mengapa LSBS Universitas Islam Bandung mengadakan pelestarian budaya dan seni Sunda. Dengan menggunakan teori interaksi sosial, dan juga metode penelitian kualitatif studi kasus. Pengumpulan data dilakukan melalui observasi dan wawancara mendalam. Model interaktif yang terdiri dari reduksi data, penyajian data serta penarikan kesimpulan digunakan untuk mengolahan data hasil observasi dan wawancara mendalam. Dari hal tersebut peneliti menemukan bahwa terdapat komunikasi verbal dan nonverbal, adanya strategi komunikasi dalam pelatihan tiga bidang, kerjasama, asimilasi dan akomodasi sebagai cara penyelesaian hambatan selain itu terdapat pula perbedaan latar belakang yang menumbuhkan kepedulian LSBS Unisba terhadap Kesenian dan Kebudayaan Sunda, dimana budaya sunda mampu mendorong kegiatan positif sedangkan seni digunakan sebagai sarana ekspresi diri.